2016
DOI: 10.1016/j.biopsych.2015.08.021
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Brain Cannabinoid Receptor Availability in Schizophrenia

Abstract: BACKGROUND Several lines of evidence suggest the presence of abnormalities in the endocannabinoid (eCB) system in schizophrenia (SCZ). However, there are limited in vivo measures of the eCB system in SCZ. METHODS Twenty five male SCZ subjects (SCZs), 18 antipsychotic treated [SCZ-MED] and 7 antipsychotic free [SCZ-UNMED]) were compared to 18 age- matched male healthy control subjects (HCs). Subjects underwent one Positron Emission Tomography (PET) scan each with the cannabinoid receptor-1 (CB1R) selective ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
73
3
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(80 citation statements)
references
References 68 publications
2
73
3
1
Order By: Relevance
“…Several post-mortem studies demonstrate that individuals with schizophrenia have highly abnormal CB 1 receptor expression patterns in the PFC (Dalton et al, 2011; Dean et al, 2001; Eggan et al, 2010; Volk et al, 2014). Furthermore, neuroimaging evidence suggests there are widespread alterations in CB 1 receptor levels in patients with schizophrenia (Ceccarini et al, 2013; Ranganathan et al, 2016; Wong et al, 2010), including significantly reduced levels in the hippocampus (Ranganathan et al, 2016). While PFC dysfunction is primarily thought to underlie cognitive deficits, hippocampal dysfunction is associated with both positive and negative (e.g.…”
Section: Cannabinoid Modulation Of Mesocorticolimbic Dopamine Tranmentioning
confidence: 99%
“…Several post-mortem studies demonstrate that individuals with schizophrenia have highly abnormal CB 1 receptor expression patterns in the PFC (Dalton et al, 2011; Dean et al, 2001; Eggan et al, 2010; Volk et al, 2014). Furthermore, neuroimaging evidence suggests there are widespread alterations in CB 1 receptor levels in patients with schizophrenia (Ceccarini et al, 2013; Ranganathan et al, 2016; Wong et al, 2010), including significantly reduced levels in the hippocampus (Ranganathan et al, 2016). While PFC dysfunction is primarily thought to underlie cognitive deficits, hippocampal dysfunction is associated with both positive and negative (e.g.…”
Section: Cannabinoid Modulation Of Mesocorticolimbic Dopamine Tranmentioning
confidence: 99%
“…In the CNS, the CB1R plays an important role in cognition 22 and has been implicated in mood and anxiety disorders 23,24 . Recent evidence from both our group and others suggests that central CB1R availability is altered psychosis [25][26][27] . We recently showed that CB1R availability is altered in patients with psychosis, where greater reductions in CB1R levels are associated with greater symptom severity and poorer cognitive functioning 27 .…”
Section: Introductionmentioning
confidence: 57%
“…A postmortem study corroborated this finding . In contrast, another PET investigation reported a decrease in CB1 binding in schizophrenic patients compared to controls . These divergent findings might be related to the gender, sex, and age of the subjects, the different affinity and pharmacokinetics of PET traces, the disease duration, and the substance abuse .…”
Section: Schizophrenia and Endocannabinoid Systemmentioning
confidence: 70%